Evaluasi Struktur dan Kebahasaan Buku “Sahabatku Indonesia Level 4” Berdasarkan CEFR dan UKBI dalam Pembelajaran BIPA Tingkat Madya (B2) - Mutiara Bella Luthfiyani; Desti Fatin Fauziyyah; Yeni Cania Puspita (Pusat riset dan Inovasi Nasional, 2025)
Learning Indonesian for Foreign Speakers (BIPA) requires structured, communicative, and internationally standardized teaching materials. One widely used teaching material is Sahabatku Indonesia Level 4, which is intended for the intermediate level. The urgency of this research lies in the importance of ensuring that the teaching materials not only convey language formally, but also align with the needs of learners' communicative competence and recognized standards, such as the Common European Framework of Reference (CEFR) level B2 and the Indonesian Language Proficiency Test (UKBI). The purpose of this research is to evaluate the structure and linguistic aspects of the Sahabatku Indonesia Level 4 teaching materials by reviewing the integration of the material, clarity of discourse, vocabulary diversity, and grammatical accuracy used. The research method used is descriptive qualitative. Data were analyzed using an evaluation rubric based on CEFR B2 and UKBI components. The focus of the analysis includes the integration of presentation between units, the logical flow of learning, and the consistency of language use in supporting receptive and productive skills. The results show that the material presentation structure reflects a logical, progressive learning sequence and supports language skill mastery. The language elements used are generally appropriate for the intermediate level, although discrepancies were still found, such as the use of irrelevant illustrations and inconsistent language style. Furthermore, the syntactic complexity in some sections still needs to be adjusted to align with the abilities of B2 learners.